2018
DOI: 10.1016/j.atmosenv.2018.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of a Chemical Mass Balance model for PM2.5 to source profiles for differing styles of cooking

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Although poor agreement of OC ck was found between the EG method and the CMB model, the former correlated better with results from the application of PMF to AMS/ACSM data (slope = 0.74, R 2 = 0.61). It has previously been shown that discrepancies exist between the CMB and PMF model (Reyes-Villegas, et al, 2018;Yin et al, 2015), whereas CMB may not be sensitive enough to the source profile of cooking aerosols (Abdullahi et al, 2018). Overall, the EG method resolves primary and secondary sources of OC well.…”
Section: Cmb Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Although poor agreement of OC ck was found between the EG method and the CMB model, the former correlated better with results from the application of PMF to AMS/ACSM data (slope = 0.74, R 2 = 0.61). It has previously been shown that discrepancies exist between the CMB and PMF model (Reyes-Villegas, et al, 2018;Yin et al, 2015), whereas CMB may not be sensitive enough to the source profile of cooking aerosols (Abdullahi et al, 2018). Overall, the EG method resolves primary and secondary sources of OC well.…”
Section: Cmb Resultsmentioning
confidence: 90%
“…The method of 14 C measurement of carbonaceous aerosols has been described elsewhere (Agrios et al, 2015;Levin et al, 2010;Szidat et al, 2014;Vlachou et al, 2018;Zhang et al, 2012Zhang et al, , 2016Zotter et al, 2014). The 14 C of TC and WINSTC was measured using a one-step protocol under pure O 2 (99.9995 %) at 760 • C for 400 s (Vlachou et al, 2018) using an elemental analyser coupled with the accelerator mass spectrometer Mini Carbon Dating System (MICADAS) at the Laboratory for the Analysis of Radiocarbon (LARA; University of Bern) (Zhang et al, 2012;Szidat et al, 2014).…”
Section: Radiocarbon ( 14 C) Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It had previously been shown that discrepancies existed between CMB and PMF model in the quantification of OCck. ACSM-PMF may overestimate OCck by approximately 2 times (Reyes-Villegas, et al, 2018;Yin et al, 2015), whereas, CMB may not be sensitive enough to the source profile of cooking aerosols (Abdullahi et al, 2018). Overall, the EG method resolves primary and secondary sources of OC well.…”
Section: Other Sources Of Oc and Consistency With Cmb And Ascm-pmf Momentioning
confidence: 96%
“…In other cases, the combination of remote sensing and hydrological characteristics provides a new approach to calculate the annual load of pollution sources [ 24 ]. Among the above methods, the CMB model requires a complete spectrum of emission source components, which is difficult to ascertain in reality, and the isotope method is limited to some extent by its high equipment requirements and complex analysis process [ 25 ]. Numerical modeling requires a comprehensive understanding of the transportation and transformation mechanisms of the pollutants, as well as a large amount of data to support it [ 26 ].…”
Section: Introductionmentioning
confidence: 99%